A Study on Factors Affecting Customer Satisfaction at McDonald’s Restaurants - Rumagit, Merry C. N.; Song, Ng Hee; Farzana, Anis; Kee, Daisy Mui Hung; Annaletchumi, Annaletchumi; Zuraya, Anis; Sofea, Anis; Nathania, Nathania (International Journal of Tourism and Hospitality in Asia Pasific, 2022)
The objective of this paper is to examine the relationship between services quality, food quality, information quality, personnel quality, timeliness and cleanliness, and customer satisfaction. Customer satisfaction is crucial to the success of the business. This paper shows a discussion on how McDonald’s employees give their best when serving customers. It is widely acknowledged that McDonald’s is a well-known fast-food brand for the food & beverages industry. By focusing on the six factors, McDonald’s can ensure a high level of customer satisfaction which can lead to customer loyalty. This paper proposes a theoretical framework for this research. This paper uses a quantitative method to survey customer perception. It is expected that the six factors will significantly affect customer satisfaction.